PEMANFAATAN PEKARANGAN RUMAH UNTUK TANAMAN HOLTIKULTURA SEBAGAI STRATEGI WIRAUSAHA KREATIF BAGI MASYARAKAT KELURAHAN SANDBILIK - Rati Pundissing; Chrismesi Pagiu; Dian Intan Tangkeallo; Dwibin Kannapadang (Indonesian Collaboration Journal of Community Services, 2021)
Real Work Lecture or abbreviated as KKN is a form of community service activities carried out by students guided by one of the guidance lecturers with a cross-scientific and sectoral approach at certain times and regions. This KKN activity aims to 1) KKN during this pandami period is a form of UKI Toraja's contribution to prevent the transmission of Covid-19 in the community with the aim of implementing KKN to make the role of students as part of the community in helping the social government to socialize and implement health protocols to prevent the spread of Covid-19. 2) as a medium of learning and fostering a sense of student concern for the problems faced by the community and reminding the public to remain active in improving the economy during the pandemic. This KKN activity is based on one core program in agriculture, namely "Utilization of Home Yards for Horticultural Crops as a Creative Entrepreneurial Strategy for Sandabilik Village Communities" and several other additional programs. The method used in this activity is to use a participatory approach that is to carry out community education and training with academics (Lecturers, students and government) acting as facilitators to be able to learn from each other, share their knowledge and experience. The location of the activity is Sandabili Village of South Makale Subdistrict.  The number of students involved in this activity consists of 14 students from different study programs. While the partners of this activity are the mothers of the chairmen of the guesthouse and the village apparatus. The implementation of this activity consists of several programs, namely the core program of agriculture, namely "Utilization of Home Yards for Horticultural Plants as a Creative Entrepreneurial Strategy for the Sandabilik Village Community" and several other additional programs as follows: a) Spraying Disinfectants in people's homes, b) Assisting the Covid Task Force in the enforcement operation of Covid-19 and PPKM health protocols, c) Distribution of assistance for residents who are self-isolated (isoman),   d) Assisting the village in collecting people who have not been vaccinated and taking part in the implementation of vaccinations, e) Spirituality services, f) Learning assistance, h) The creation of pilot cages, i) Sports activities in pandemic times